Geography Matters in Ancient Egypt - Melanie Waldron (Raintree, 2015)
How did the River Nile shape Egyptian life? What is a shaduf and what was it used for? How did the Ancient Egyptians make papyrus paper? Geography Matters in Ancient Egypt looks at how the Egyptian Empire changed through time and gives fascinating insights into many different aspects of Egyptian life through its geography. Read about how the Egyptians made use of desert oases, how they found and used resources such as limestone and granite for building pyramids in desert areas, and how early Egyptian settlers who had decided to build in areas around the River Nile prevented their houses from flooding.
Keywords: Non-fiction -- Non-fiction